Thickness-dependent stabilization of tetragonal ZrO2 in oxidized zirconium. (1st March 2018) - Harlow, Wayne; Lang, Andrew C.; Demaske, Brian J.; Phillpot, Simon R.; Taheri, Mitra L.
Abstract: Here we describe a study on the effect of transmission electron microscopy sample preparation on the stability of the tetragonal ZrO2 phase, as determined by precession electron diffraction. It was found that sample thickness, and thus corresponding stress remaining within the sample, can significantly affect the percentage of tetragonal phase ZrO2 recorded in the oxide layers. The microscopy-based finding is complemented by density functional theory calculations, confirming that there exists a crossover in energy between the two phases that depends on compressive strain. These findings further confirm that the significant portion of tetragonal phase is the result of stress stabilization. Graphical abstract: